When students become patients: TB disease among medical undergraduates in Cape Town, South Africa - van der Westhuizen, H; Dramowski, A (Health and Medical Publishing Group, 2017)
Background. Medical students acquire latent tuberculosis (TB) infection at a rate of 23 cases/100 person-years. The frequency and impact of occupational TB disease in this population are unknown. Methods. A self-administered questionnaire was distributed via email and social media to current medical students and recently graduated doctors (2010 - 2015) at two medical schools in Cape Town. Individuals who had developed TB disease as undergraduate students were eligible to participate. Quantitative and qualitative data collected from the questionnaire and semi-structured interviews were analysed with descriptive statistics and a framework approach to identify emerging themes. Results. Twelve individuals (10 female) reported a diagnosis of TB: pulmonary TB (n=6), pleural TB (n=3), TB lymphadenitis (n=2) and TB spine (n=1); 2/12 (17%) had drug-resistant disease (DR-TB). Mean diagnostic delay post consultation was 8.1 weeks, with only 42% of initial diagnoses being correct. Most consulted private healthcare providers (general practitioners (n=7); pulmonologists (n=4)), and nine underwent invasive procedures (bronchoscopy, pleural fluid aspiration and tissue biopsy). Substantial healthcare costs were incurred (mean ZAR25 000 for drug-sensitive TB, up to ZAR104 000 for DR-TB). Students struggled to obtain treatment, incurred high transport costs and missed academic time. Students with DR-TB interrupted their studies and experienced severe side-effects (hepatotoxicity, depression and permanent ototoxicity). Most participants cited poor TB infection-control practices at their training hospitals as a major risk factor for occupational TB. Conclusions. Undergraduate medical students in Cape Town are at high risk of occupationally acquired TB, with an unmet need for comprehensive occupational health services and support.